2016
DOI: 10.1039/c6ra04856k
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and dual dose-dependent antigenotoxic and genotoxic properties of an ethanol extract of propolis

Abstract: Propolis is a resinous product made by honeybees from plant-derived materials, with high content of polyphenols associated to beneficial bioactivities with potential use as a natural food additive for preservation and as a functional food ingredient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…Even though these ingredients are already being used in cosmetics, the lack of antigenotoxicological studies makes it crucial to investigate further how to incorporate them in cosmetics to benefit human health. Studies have shown that plants, fruits, and vegetables with antigenotoxic properties show promising results for the cosmetic industry [ 193 , 194 , 195 ]. Additional investigation can be carried out, namely, evaluating the cosmetic properties of the natural ingredients towards promoting DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these ingredients are already being used in cosmetics, the lack of antigenotoxicological studies makes it crucial to investigate further how to incorporate them in cosmetics to benefit human health. Studies have shown that plants, fruits, and vegetables with antigenotoxic properties show promising results for the cosmetic industry [ 193 , 194 , 195 ]. Additional investigation can be carried out, namely, evaluating the cosmetic properties of the natural ingredients towards promoting DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, propolis was widely used as a folk medicine worldwide since ancient times. Propolis is known to possess valuable biological properties (Sforcin 2016;Cornara et al 2017) such as antibacterial (Oliveira et al 2017;Roh and Kim 2018), antioxidant (Cruz et al 2016), anti-inflammatory (Moreira et al 2008), antineurodegenerative (Falca ˜o et al 2010), anti-tumor (Silva-Carvalho et al 2014, antifungal (Roh and Kim 2018), anti-protozoan (Falca ˜o et al 2014), anti-viral (Yildirim et al 2016), hepato-protective (Sheng et al 2007), local-anesthetic (Moreira et al 2008, and free-radical-scavenging (Al-Ani et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The treated and untreated cells were washed with, and resuspended in, phosphate buffer, then 10-times diluted and added to 10 μM DCFDA (Sigma-Aldrich) in 1% DMSO. DCFDA, as a lipophilic compound, permeates the metabolically active cell [ 39 ]. Once oxidized by ROS, DCFDA is converted to a highly fluorescent DCF, which fluoresces at 527 nm, and thus provides an estimate of ROS levels [ 40 ].…”
Section: Methodsmentioning
confidence: 99%